The Acceptability and Initial Effectiveness of ?Space from Money Worries?: An Online Cognitive Behavioural Therapy Intervention to Tackle the Link Between Financial Difficulties and Poor Mental Health. - Richards, Derek (My University, 2022)
Background: Previous research has shown a strong relationship between financial difficulties and mental health problems. Psychological factors such as hope and worry about finances appear to be an important factor in this relationship. Objective: To develop an online based psychological intervention (Space from Money Worries) to tackle the psychological mechanisms underlying the relationship between poor mental health and financial difficulties, and to conduct an initial evaluation of the acceptability and preliminary efficacy of the intervention. Materials and Methods: 30 participants accessing Increasing Access to Psychological Therapies (IAPT) services completed GAD-7 to measure anxiety and PHQ-9 to measure depression upon signing up to the online intervention and again 4 to 8 weeks after this. Participants also completed a measure of perceived financial distress/wellbeing and a “Money and Mental Health Scale” constructed for the evaluation. Results: Overall, 77% (n = 23) completed the intervention and follow-up assessments. Intent to Treat Analysis showed that there were statistically significant improvements in symptoms of depression, anxiety, improved perceived financial wellbeing and reduced scores on the money and mental health scale. The vast majority of participants rated each module positively. Conclusions: Space from Money Worries appears to be acceptable and may lead to improvements in mental health, perceived financial wellbeing and a reduced relationship between financial difficulties and poor mental health. However, future research with a larger sample and a control group are needed to confirm that these changes are due to the intervention.
PUBLISHED
Keywords: Online CB; Computer-based CBT; Mental health; Anxiety; Depression; Debt; Financial difficulties; Poverty